Juan Sánchez Cotán’s Still Lifes and Artistic Ingenio in Early Modern Toledo - Carmen Ripollés (Boletín del Museo del Prado)
This essay brings new light on the creation and early reception of the still lifes of the Toledan painter Juan Sánchez Cotán. It focuses on Cotán’s friendship with and professional relationship to the metalworker Diego de Valdivieso and the manuscript illuminator Juan de Salazar, both of whom are recorded as being among the first owners of his still lifes. An analysis of these artists’ works vis-j-vis Cotán’s still lifes reveals similar technical and conceptual concerns, as well as a shared will to elevate their crafts to demonstrate ingenio. This analysis therefore places Cotán’s still lifes in the context of artistic experimentation, supporting the long-held assumption that his first patrons appreciated these pictures foremost as ingenious novelties.